Phylogeny of Celastraceae Subfamily Salacioideae and Tribe Lophopetaleae Inferred from Morphological Characters and Nuclear and Plastid Genes - Coughenour, Jennifer M.; Simmons, Mark P.; Lombardi, Julio A. [UNESP]; Cappa, Jennifer J. (Amer Soc Plant Taxonomists, 2010)
The phylogeny of Celastraceae subfamily Salacioideae (ca. 255 species in the Old and New World tropics) and tribe Lophopetaleae (ca. 29 species in southern Asia and the Austral-Pacific) was inferred using morphological characters together with plastid (matK, trnL-F) and nuclear (ITS and 26S rDNA) genes. Brassiantha, a monotypic genus endemic to New Guinea, is inferred to be more closely related to the clade of Dicarpellum (New Caledonia) and Hypsophila (Queensland, Australia) than it is to Hippocrateoideae or Salacioideae. This unambiguously supported resolution indicates that a nectary disk positioned outside the stamens has been convergently derived in these two lineages. The clade of Kokoona and Lophopetalum is resolved as more closely related to Breria and Elaeodendron than it is to Hippocrateoideae or Salacioideae. Sarawakodendron, a monotypic genus endemic to Borneo, is resolved as sister to Salacioideae. Salacioideae are inferred to have an Old World origin that was followed by a single successful radiation within Central and South America. We infer that capsular fruits are primitive within the clade of Hippocrateoideae + Sarawakodendron + Salacioideae, with berries a synapomorphy for Salacioideae. Based on the resolution of Sarawakodendron as sister to Salacioideae, we hypothesize that the filaments of Sarawakodendron arils are homologous to the spiral filaments in the mucilagenous pulp of Salacioideae.
Keywords: aril homology; Brassiantha; Kokoona; local alignment; Lophopetalum; Sarawakodendron